Peningkatan Ketrampilan Siswa Sekolah Dasar Dengan Pemanfaatan Limbah Kertas Di Era Pandemik - Mahsunah E Rahayuningsih; Masriah; Septina Dwi Retnandari; Christine Widi Lestari (Unika Santu Paulus Ruteng, 2023)
The 2020 community service project, which took place in Gajahmungkur, Semarang, had as its focus on paper waste processing among schoolchildren. By deploying numerous lecturers at the Indonesian State Maritime Polytechnic, it is expected that school pupils who are dissatisfied with online learning activities will be provided with a training program to produce paper flowers from waste disposal. The instructors have come up with a plan to encourage primary school children to create handicrafts like colorful, appealing paper flowers out of discarded paper. This approach was chosen to lessen the negative effects of waste and enhance environmental hygiene while also diverting activities that are less beneficial for students, such using devices for gaming and watching less instructive shows. Ten elementary school kids in Bendan Dhuwur, Gajahmungkur, Semarang are the audience target for this community service activity. In conclusion, by taking part in this program, kids can transform their pointless activities into innovative, creative ones. Utilizing paper trash can also improve the environment's cleanliness and comfort. The benefits of this volunteer work were that the elementary school student was amused and was able to redirect his addiction to gadgets amid a pandemic.